Platelet Profile as Prognostic Factor in Critically ill Children - Yanni, Gema Nazri; Saragih, Rina Amalia C (Open Access Macedonian Journal of Medical Sciences, 2020)
BACKGROUND: Previous studies showed that platelet profile may reflect the platelet function better than the platelet count itself, but the study on its use as a prognostic indicator in critically ill children is still limited. AIM: We analyzed the association between platelet profile such as platelet count, plateletcrit (PCT), mean platelet volume (MPV), and platelet distribution width (PDW) and mortality, also its correlation with pediatric logistic organ dysfunction-2 (PELOD-2) score in critically ill children admitted to the pediatric intensive care unit (PICU). METHODS: A prospective cohort study was conducted in PICU Haji Adam Malik General Hospital, Medan. Assessment of platelet profile (platelet count, PCT, MPV, and PDW) and PELOD score on the 1st and 3rd day of PICU admission were performed. RESULTS: Eighty-three subjects were recruited in this study, 44 were boy with a median age of 6 (1–17) years old. The septic patient was 43 subjects (51.8%). Platelet count on the 1st day (p = 0.024) and PDW on the 3rd day (p = 0.018) of PICU admission was significantly associated with mortality. There was no correlation between platelet profile and PELOD-2 score on day 1 and 3. However, the difference between MPV on days 1 and 3 (ΔMPV) significantly correlated with the change of PELOD-2 score (r = 0,647, p < 0.0001). CONCLUSION: Platelet count on 1st day and PDW on the 3rd day had a significant association with mortality but no correlation between platelet profile and PELOD-2 score.